Rhizobium host specificities in phaseolus coccineus L. and phaseolus vulgaris L. - Hohenberg, J.S.; Munns, D.N.; Tucker, C.L. (1982)
The introduction of desirable agronomic characteristics into Phaseolus vulgaris L. is being attempted by interspecific hybridization with P. coccineus, but the effects on root nodulation are unknown. Accordingly, cross-inoculation relationships between P. vulgaris ‘Red Kidney’ and P. coccineus ‘Scarlet Runner’ were tested in the greenhouse with a group of 16 Rhizobium strains effective on Red Kidney and a group of 12 strains effective on Scarlet Runner. Both groups had diverse origins, including commercial sources and isolations from bean fields and other sites in California. Only six strains, all isolates from Scarlet Runner, were effective on both hosts. Fifty percent of Scarlet Runner isolates were as effective on Red Kidney as the more effective of Red Kidney's homologous strains. Thirty percent of the California isolates tested on Red Kidney were more effective than two commercial inocula. Strain rejection in Red Kidney was expressed in 75% of all cases as failure to form nodules. In contrast, strain rejection by Scarlet Runner was expressed in 64 to 68% of all cases as ineffective nodulation (nodule malfunction). If Scarlet Runner is representative of P. coccineus in this respect, interspecific hybridization is likely to increase rather than reduce the tendency of P. vulgaris to nodulate with ineffective rhizobia.